The Effectiveness of Positive Psychotherapy on Perceived Stress, Health Anxiety, and Hope in Women with Breast Cancer - Karimpoorian, Hadis; Kordmirza Nikoozadeh, Ezzatollah; Rafiepoor, Amin (Psychology of Woman Journal, 2025)
Objective: This study aimed to investigate the effectiveness of positive psychotherapy in reducing perceived stress and health anxiety while enhancing hope among women diagnosed with breast cancer. Methods and Materials: A randomized clinical trial with a non-equivalent group design was conducted in Tehran in 2023. The sample consisted of 30 women with breast cancer who were selected through purposive sampling and randomly assigned to one of two experimental groups receiving positive psychotherapy or a control group. The intervention consisted of ten 90-minute sessions based on Seligman’s (2006) positive psychotherapy protocol. Data were collected using the Perceived Stress Scale (PSS), the Health Anxiety Inventory (HAI), and Snyder’s Hope Scale. All assessments were performed at three stages: pretest, posttest, and a follow-up. Data analysis was performed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS v22. Findings: Multivariate analysis of variance indicated a significant interaction between time and group for all outcome variables (p < 0.001). Repeated measures ANOVA showed significant reductions in perceived stress (F = 70.48, p < 0.001, η² = 0.71) and health anxiety (F = 120.30, p < 0.001, η² = 0.81), and a significant increase in hope (F = 70.50, p < 0.001, η² = 0.71) in the experimental group compared to the control group. Bonferroni post-hoc tests confirmed significant improvements from pretest to both posttest and follow-up stages in all three variables for the experimental group. Conclusion: The findings support the effectiveness of positive psychotherapy in significantly improving psychological outcomes among women with breast cancer. This intervention offers a viable therapeutic approach to mitigate stress and anxiety while fostering hope, thereby enhancing psychological well-being in this population.